Without distinction - Dusapin, Alice (Christophe Daviet-Thery, 2016)
« Museums generally use display cases as a neutral presentation format that is pushed into the background, so that full justice is done to the objects they contain. In the pictures, they are shown for what they are, an arrangement of display cases from different museums and institutions from Belgium. » Oriol Vilanova